2015
DOI: 10.3109/09637486.2015.1064873
|View full text |Cite
|
Sign up to set email alerts
|

Snack patterns are associated with biomarkers of glucose metabolism in US men

Abstract: Few studies have made distinctions between dietary intake from meals and snacks in relating them to biomarkers. We aimed to examine if snack patterns are associated with biomarkers of glucose metabolism, specifically hemoglobin A1c and HOMA-IR in US adults. Using 24-h dietary recall data from National Health and Nutrition Examination Survey (NHANES) in 2007-2008, we derived snack patterns using factor analyses. Multivariate logistic regressions were performed to estimate adjusted odds ratios (AOR) for biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Despite each study being conducted in distinct geographic regions with different recruitment methods and criteria, the same two patterns were independently identified in three of the four studies. These two patterns are not consistent with those derived among adults in NHANES (17,18) , but patterns for the remaining COPTR study (IMPACT) were similar to two of the six patterns derived using NHANES 2007-2008 data (18) . The IMPACT study was unique in recruiting the oldest sample of participants in COPTR and being predominantly non-Hispanic Black.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Despite each study being conducted in distinct geographic regions with different recruitment methods and criteria, the same two patterns were independently identified in three of the four studies. These two patterns are not consistent with those derived among adults in NHANES (17,18) , but patterns for the remaining COPTR study (IMPACT) were similar to two of the six patterns derived using NHANES 2007-2008 data (18) . The IMPACT study was unique in recruiting the oldest sample of participants in COPTR and being predominantly non-Hispanic Black.…”
Section: Discussioncontrasting
confidence: 69%
“…Such an approach may provide a better indication of how foods/beverages consumed during snack occasions interact to affect overall diet quality (16) . Snack-occasion-specific dietary patterns have been derived using adult populations in the USA and these patterns have been differentially associated with cardiometabolic risk (17,18) and obesity (17) . Therefore, deriving these patterns for a child population may provide valuable insight into the intake of children and potentially clarify how intake during snack occasions is associated with diet quality and obesity in this age group.…”
mentioning
confidence: 99%
“…It shows that two dietary patterns were identified in 9 of the 22 studies, with the two most often identified patterns being the Healthy and the Western patterns (Hu et al, 2000; van Dam et al, 2002; Perrin et al, 2005; Wu et al, 2006; McNaughton et al, 2007; Varraso et al, 2007; Campbell et al, 2008; Lau et al, 2008; Chan et al, 2013; Bai et al, 2015; Arabshahi et al, 2016; Ax et al, 2016). Five of 22 studies identified three dietary patterns (Tseng et al, 2004; Ambrosini et al, 2008; Charreire et al, 2011; Ruusunen et al, 2014; Shin et al, 2015). In all 22 studies, a Healthy pattern or a Prudent pattern or a dietary pattern rich in fruit and vegetables was identified, a pattern rich in meat was identified six times, and the Modified Western – Sweet pattern was never reported.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is limited data regarding snack patterns and their association with metabolic disorders. A previous study suggested that the "dairy and sugar pattern" was associated with a higher risk of elevated glycated hemoglobin and insulin resistance in adult men (11). Another study showed an inverse association between "milk desserts pattern" and values of waist circumference (WC) (12).…”
Section: Introductionmentioning
confidence: 99%